2007
DOI: 10.1016/j.cmet.2007.09.009
|View full text |Cite
|
Sign up to set email alerts
|

The E3 Ligase MuRF1 Degrades Myosin Heavy Chain Protein in Dexamethasone-Treated Skeletal Muscle

Abstract: Skeletal muscle atrophy occurs as a side effect of treatment with synthetic glucocorticoids such as dexamethasone (DEX) and is a hallmark of cachectic syndromes associated with increased cortisol levels. The E3 ubiquitin ligase MuRF1 (muscle RING finger protein 1) is transcriptionally upregulated by DEX treatment. Differentiated myotubes treated with DEX undergo depletion of myosin heavy chain protein (MYH), which physically associates with MuRF1. This loss of MYH can be blocked by inhibition of MuRF1 expressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

27
503
5
5

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 571 publications
(540 citation statements)
references
References 37 publications
27
503
5
5
Order By: Relevance
“…In addition, both mRNA expression and protein level of MuRF1 were up-regulated, while no change in the expression of Atrogin1 was observed, in the muscle tissue from Smad3-null mice when compared to controls ( Figure 4A and 4B). MuRF1 has been previously demonstrated to interact with and promote the degradation of MyHC protein in myotubes treated with dexamethasone (DEX) [25]. Consistent with this, we find decreased expression of MyHC at the protein level in Smad3-null mice, with no appreciable change in mRNA expression of MyHC detected between WT and Smad3-null muscle tissue ( Figure 4A and 4B).…”
Section: Increased Ubiquitination Of Proteins In Smad3-null Skeletal supporting
confidence: 77%
See 1 more Smart Citation
“…In addition, both mRNA expression and protein level of MuRF1 were up-regulated, while no change in the expression of Atrogin1 was observed, in the muscle tissue from Smad3-null mice when compared to controls ( Figure 4A and 4B). MuRF1 has been previously demonstrated to interact with and promote the degradation of MyHC protein in myotubes treated with dexamethasone (DEX) [25]. Consistent with this, we find decreased expression of MyHC at the protein level in Smad3-null mice, with no appreciable change in mRNA expression of MyHC detected between WT and Smad3-null muscle tissue ( Figure 4A and 4B).…”
Section: Increased Ubiquitination Of Proteins In Smad3-null Skeletal supporting
confidence: 77%
“…Alternatively, this could be due to an increase in the activity of NF-κB transcription factors, which can be activated by inflammatory cytokines [14,35]. Consistent with increased MuRF1 levels, MyHC, a known target of MuRF1 [25], was down-regulated ( Figure 4A and 4B). Thus, these results clearly suggest that the muscular atrophy seen in Smad3-null mice is much akin to cachecticlike muscle wasting.…”
Section: Muscle Atrophy Seen In Smad3-null Muscles Could Be Due To Insupporting
confidence: 58%
“…Importantly, additional experiments also provided evidence that the compound was able to prevent the reduction in both the content and ubiquitination of the key sarcomeric protein actin and a corresponding significant reduction in the activity of the ubiquitin proteasome pathway. Interestingly, while myosin heavy chain is generally suggested to be the key target of MuRF1‐mediated degradation,6, 15 other studies have also found that actin is similarly susceptible40: In vitro and in vivo data have demonstrated lower protein content in line with a greater ubiquitination of actin in catabolic conditions, with MuRF1 found to interact with and polyubiquitinate actin. As such, our data provide strong support that the developed compound was able to perturb the myofibril‐directed MuRF1 atrophy axis, which, in turn, inhibited actin ubiquitination and degradation and thus overall muscle proteolysis.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have reported that small‐molecule knockdowns of MuRF1 can prevent atrophy ex vivo in myotubes 13, 14, 15. However, to our knowledge, this concept had yet to be translated to an in vivo setting, such as animal models that mimic clinically relevant disease conditions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation